Christmas in the crosshairs: two thousand years of denouncing and defending the world's most celebrated holiday - Bowler, Gerry (Oxford University Press, 2017)
The inventors -- The revivalists -- The tyrants -- The godly and the godless -- The appropriators -- The discontented -- The privatizers